Metode Emo Demo Meningkatkan Pengetahuan dan Sikap Cuci Tangan Pakai Sabun (CTPS) pada Anak Usia Sekolah - Ade Rosita; Dahrizal Dahrizal; Widia Lestari (Poltekkes Kemenkes Bengkulu, 2021)
The population of children in Indonesia is an average of 30% of the total population of Indonesia and children of elementary school age are the largest compared to others. There are 40.2% in Indonesia and around 54.2% in the City who have the habit of washing their hands. The COVID-19 pandemic is a threat to the health of all people, including school-age children. Emo Demo is a method of educating the public developed by the Global Alliance for Improved Nutrition .Handwashing with Soap is a program of the Ministry of Health in changing clean and healthy living behavior. This study aimed to identify the effect of the emo demo method on the knowledge and attitudes of CTPS in school-age children. The research design was a quasi-experimental with a pre-post test design with a control group. Data collection tools used questionnaires and observation sheets. CTPS education using the Emo Demo method was given once for 20 minutes to each group using display cards and simulated germicidal fluid and hand washing tools. The research sample consisted of 70 people consisting of 35 people in the intervention group and 35 in the control group. The analysis showed that there was a significant difference in the increase in the average value of knowledge and attitudes about CTPS in school-age children. Based on these results, it is expected that the use of learning media for school-age children is not monotonous, the Emo Demo method can be used as a method of education for school-age children.